The Drama of Language Essays on Goethe and Kleist - Burckhardt, Sigurd (Johns Hopkins University Press, 2019)
Originally published in 1970. For Sigurd Burckhardt, literary interpretation began with the discovery of an "inconsistency" in a text. Minimizing the possibility that the writer has "unconsciously" fallen into an inconsistency in the use of material, the true interpreter, Burckhardt believes, abandons a tendency to "correct" the writer and seeks instead a new formulation by which the inconsistency can be seen as a part of a work's essential unity. "Whether I search for the meaning of a word or for the meaning of my life," he wrote, "I am looking for something under which I can subsume the otherwise unrelated and meaningless particular so as to place it in a larger order." That method, so characteristic of Burckhardt's criticism, underlies his studies of Goethe and Kleist and unifies the essays of this volume. Prior to his death in December 1966, Professor Burckhardt had considered the possibility of collecting his writings on Goethe and Kleist. One essay had never been published; others had appeared only in German or were available in scattered sources. The preparation of the essays for publication, a service of professors Bernhard Blume and Roy Harvey Pearce, makes possible this impressive demonstration of their late colleague's interest in German literature. The seven critical studies are introduced by an essay that makes explicit the concern for language implicit throughout the volume. Burckhardt proceeds by close adherence to the text and by analysis of its writer's use of language and structure. He interprets Goethe's Prometheus, Pandora, Iphigenie, Tasso, Die natürliche Tochter, and Egmont and Kleist's Prinz Friedrich von Homburg and Die Hermannsschlacht. He provides original and challenging interpretations, shaping each into a self-contained entity.